Effects of Groove Feature on Shear Behavior of Steel-Sand Interface - Jukun Guo; Xiaowei Wang; Shengyou Lei; Rui Wang; Hailei Kou; Daokai Wei (Advances in Civil Engineering)
Surface groove morphology of structure and particle distribution of soil had a significant effect on the surface friction of structure. In order to investigate the interface shear stress-shear displacement curves, interface model and interface shear strength index when normal stress, groove width, and groove angle change, the interface shear tests of standard sand with steel plates are performed using an improved direct shear apparatus. Test results indicate that the peak shear stress increases with normal stress and the intersection angle between groove direction and shear direction. When the angle increases by 45°, the peak shear stress increases range from 4% to 13%. The peak shear stress increases with groove width, for every 1 mm increase in groove width, and the increasing extent of peak shear stress ranges from 4% to 22%, 3% to 13%, and 1% to 6%, respectively. When the groove angle is 45° and 90°, the increasing extent of peak shear stress decreases with groove width, but when the groove angle is 0°, the decrease regularity of peak shear stress increasing extent is not obvious. The hyperbolic model and Gompertz-C model are used to study the shear stress-shear displacement curves of sand-steel interface. The ratio of the interface peak shear stress of the hyperbolic model and Gompertz-C model to that of the shear test ranges from 0.90 to 1.03 and 0.88 to 0.98, respectively. The interface friction angle at the sand-steel interface ranges from 22° to 29°, and the friction angle of the rough interface is larger than that of the smooth interface. The interface friction angle increases with the intersection angle between the groove direction and the shear direction, the largest at 90°, the second at 45°, and the smallest at 0°. Under the same groove angle, the interface friction angle increases with the groove width, for every 1 mm increase in groove width, and the increasing extent of interface friction angle ranges from 4% to 15%, 4% to 7%, and 2% to 3%, respectively. The increasing extent of interface friction angle decreases with groove width, and this change rule is more obvious at the groove angle of 45° and 90° than at 0°.